Does land use history have an influence on soil quality? A case study with agricultural lands of Rodh Mulazai, Pishin, Balochistan Pakistan - TARAN, Muhammad Tariq; GUL, Shamim; PANEZAI, Sanaullah; NASEEM, Mahrukh; SHAHEEN, Umbreen; ZIAD, Tariq; LAHGHARI, Saad Ullah Khan; CHANDIO, Tasawar Ali; KAKAR, Asmatullah; AGHA, Sadiq; PANEZAI, Anwar; PONYA, Zsolt; et al. (Food Science and Technology, 2023)
Rodh Mulazai is a small town in Pishin District, Balochistan, Pakistan. This study investigated the soil quality of agricultural lands in this region. The 20 field sites were sampled. All these sites had orchards (commonly apple), and three of them had tree-based intercropping systems with wheat or tomato. These agricultural lands were 7–25 years old and were commonly under conservation agriculture since the beginning. The concentration of soil organic matter in the upper 0–10 cm depth of these field sites ranged from 9.33 to 41 g kg-1. A total of 13 soil macrofauna species were found, and the most common and abundant was the earthworm Lumbricus terrestris, followed by the earthworm Lumbricus rubellus. There was no relationship found between the total number of soil fauna and the concentration of soil organic matter at these field sites, nor did soil organic matter have a relationship with the concentration of soil clay contents. Likewise, the age of these sites with continuous conservation agriculture had no relation to the concentration of soil organic matter.